Preparing a Resilient Generation: Challenges and Opportunities for Islamic Education in Era 5.0 - Mahfud Heru Fatoni; Sukari Sukari (Yayasan Adra Karima Hubbi, 2024)
The transition from era 4.0 to era 5.0 forces society to adapt to rapid technological changes, with various innovations emerging and demanding higher adaptability. This study aims to explore the challenges and opportunities faced by Islamic education in preparing a resilient generation in era 5.0. Using the library study method or scoping review, this study identified various relevant literature related to the challenges and opportunities of Islamic education in the midst of society 5.0. The results of the study indicate that some of the main challenges for Islamic education include: moral decadence, the proliferation of non-educational media that is easily accessible to children, inappropriate use of social media, demands to compete in various aspects of life, the need to follow the development of democracy and modernization, pressure to survive the crisis and maintain what has been achieved, and demands to compete at regional, national, and international levels. To overcome these challenges, this study suggests that Islamic education can foster a deep understanding of religion to hone spiritual and emotional intelligence, create useful content in accordance with Islamic teachings by utilizing media that is easily accessible to the wider community, strengthen Islamic education that focuses on developing children's character, provide 21st century skills to survive in the era of democracy and modernization, and prepare reliable educators who are able to innovate and think ahead.